PENGARUH PLATFORM DIGITAL TERHADAP KEMAMPUAN LITERASI NUMERASI SISWA - Sape, Herwandi; Firdaus, Andi Mulawakkan (Almeera Education, 2024)
This study aims to analyze the effect of using digital platforms on students' numeracy literacy skills. The research used a quantitative approach with a quasi-experimental design. The research subjects were grade XI students at PGRI Tamalate High School Makassar, with grade XI.A as the experimental group using the digital platform and XI.B as the control group using conventional methods. Data were collected through PISA standard-based numeracy literacy test and student and teacher perception questionnaires. Data were analyzed using descriptive and inferential statistics (t-test).The results showed that the use of digital platforms significantly improved students' numeracy literacy skills, with a significant difference in post-test scores between the experimental (85.14) and control (72.46) groups (p < 0.05). The questionnaire also revealed that students and teachers had positive perceptions of the use of digital platforms in learning. This finding is in line with technology-based learning theory that supports active interaction and student engagement in understanding numeracy concepts. This study recommends the continuous integration of digital platforms in learning, supported by teacher training and technological infrastructure improvements, to improve the quality of numeracy education in the digital era.